Penerapan Model Make A Match pada Pembelajaran Fisika Kelas X SMA Negeri 2 Kota Lubuklinggau - Endang Lovisia (SPEJ (Science and Physic Education Journal), 2017)
The purpose of this research is to know the result of physics learning of class X student of SMA Negeri 2 Lubuklinggau after application of Make a Match model. The type of research is quantitative research with quasi experimental research method, with one group pre test and post test design. The population in this study is all students of class X SMA Negeri 2 Lubuklinggau. Samples were taken randomly by drawing, so that the class X1 was obtained. Technique of collecting data using test technique. Based on the results of post-test data analysis obtained the average value of students at 79.11 with 5 percent level of disturbance obtained tcount 2.98 and ttable 1.684 for thitung great than ttable, it can be concluded that the results of physics learning class X SMA 2 Lubuklinggau after applied Model Make a Macth is significantly declared complete. Keyword : Physics, Learning result, Make a Match.